Nb-C nanocomposite films with enhanced biocompatibility and mechanical properties for hard-tissue implant applications - Yate, Luis; Coy, L. Emerson; Gregurec, Danijela; Aperador, Willian; Moya, Sergio E.; Wang, Guocheng (ACS Applied Materials and Interfaces, 2015)
One of the key challenges in engineering of orthopedic implants is to "bioactivate" their surface by using different surface techniques and materials. Carbon, especially amorphous (a-C) and diamond-like carbon down (DLC) films have attracted much attention in biomedical fields due to their biocompatibility and low coefficient of friction. However, they are unsuitable for uses as a "bioactivity enhancer" of orthopedic implants due to their bioinertness. In this work, we use the nonreactive magnetron sputtering technique to produce a-C films including the biocompatible niobium (Nb) element to alter the surface chemistry and nanotopography of the a-C films with the purpose of bioactivating the a-C film coated implants. Results show that the nanocomposite films (Nb-C) formed by the addition of Nb into the a-C films not only have improved corrosion resistance, but also possess enhanced mechanical properties (nanohardness, Youngs modulus and superelastic recovery). Preosteoblasts (MC3T3-E1) cultured on the Nb-C films have enhanced adhesion and upregulated alkaline phosphatase (ALP) activity, compared to those cultured on the a-C film and TiO2 films used as a control, which are thought to be ascribed to the combined effects of the changes in surface chemistry and the refinement of the nanotopography caused by the addition of Nb.
CRIS-Team Scopus Importer:2020-10-13
Keywords: amorphous carbon; biocompatibility; niobium; orthopedic implant; osteoblast; thin films